The Effect of Frez and Ecata Therapy on GDS Levels in Diabetes Mellitus Patients - Fauzan Widianto; Citra Indah Fitriwati (Indonesian Journal of Global Health Research, 2026)
Diabetes mellitus (DM) is a group of metabolic diseases characterized by hyperglycemia that occurs due to abnormalities in insulin secretion, insulin function, or both. Diabetes Mellitus (DM) is a group of metabolic diseases characterized by hyperglycemia that occurs due to abnormalities in insulin secretion, insulin action, or both. The incidence of DM increases significantly every years.  The aim of this study was to determine the difference in random blood sugar levels in patients before and after being given Frez and Ecata therapy. The research method used was a quasi-experimental method with a pre and post intervention and control group approach. The number of respondents in this study was 52 respondents. The sampling technique used was purposive sampling. Data collection was conducted in accordance with existing SOPs. The Zusanli foot relaxing exercise was performed once daily for one month. ECATA extract was administered in tea form at least twice daily for one month. The data analysis in this study was univariate analysis, which aims to explain each variable studied, including respondent characteristics and GDS levels. Bivariate testing used the Independent T-test. Results The results obtained in this study were changes in blood sugar levels in the intervention group after being given therapy with a p value of 0.025 and there was a difference in blood sugar levels in the intervention and control groups (p value: 0.000). Therapy to decrease blood sugar is already widely available in society. Without controlling diet, any treatment will be meaningless. One of the right ways is with Frez and Ecata therapy which changes behavior slowly and surely.